2018
DOI: 10.1038/s41388-018-0270-8
|View full text |Cite
|
Sign up to set email alerts
|

A kinome-wide high-content siRNA screen identifies MEK5–ERK5 signaling as critical for breast cancer cell EMT and metastasis

Abstract: An epithelial to mesenchymal transition (EMT) has been correlated to malignant tumor progression and metastasis by promoting cancer cell migration and invasion and chemoresistance. Hence, finding druggable EMT effectors is critical to efficiently interfere with metastasis formation and to overcome therapy resistance. We have employed a high-content microscopy screen in combination with a kinome and phosphatome-wide siRNA library to identify signaling pathways underlying an EMT of murine mammary epithelial cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 65 publications
3
36
1
Order By: Relevance
“…COX2 overexpression is associated with progression in multiple cancers, and COX2 inhibitors have shown promising therapeutic effects in clinical trials [39,40]. Furthermore, both GRB2 and MEK5/ERK5 are commonly overexpressed in breast cancer and associated with poor overall survival, and targeting of these proteins/ pathways is shown to suppress breast cancer progression [41][42][43]. Thus, downregulation of COX2, GRB2 and MEK5 as seen in the ATX-101/AEE788 combination treatment supports the phenotype observed in this pre-clinical breast cancer model.…”
Section: Discussionmentioning
confidence: 99%
“…COX2 overexpression is associated with progression in multiple cancers, and COX2 inhibitors have shown promising therapeutic effects in clinical trials [39,40]. Furthermore, both GRB2 and MEK5/ERK5 are commonly overexpressed in breast cancer and associated with poor overall survival, and targeting of these proteins/ pathways is shown to suppress breast cancer progression [41][42][43]. Thus, downregulation of COX2, GRB2 and MEK5 as seen in the ATX-101/AEE788 combination treatment supports the phenotype observed in this pre-clinical breast cancer model.…”
Section: Discussionmentioning
confidence: 99%
“…To identify all (co)TFs that are required for EMT irrespective of their differential expression, we employed a microscopy-based EMT screen that we have previously used to screen for pharmacological EMT inhibitors as well as for kinases and phosphatases required for EMT (Pavan et al, 2018). This screen is based on cytoskeleton remodeling events occurring during EMT and enabling cell migration (Figure 2A).…”
Section: High-content Microscopy Screen For (Co)tfs Essential For Emtmentioning
confidence: 99%
“…Previous studies have identified target genes for inhibiting migration and/or invasion ability of cancer cells through library screening. Pavan et al (66) developed a system combining RNAi library screening with a microscopy-based high-throughput quantitative analysis to identify a signaling pathway contributing to EMT in breast cancer. The group identified 59 genes whose inhibition suppressed transforming growth factor β-induced EMT in immortalized epithelial normal murine mammary gland cells.…”
Section: Dropout Viability Screening Under Drug Treatmentmentioning
confidence: 99%
“…The group identified 59 genes whose inhibition suppressed transforming growth factor β-induced EMT in immortalized epithelial normal murine mammary gland cells. In addition, Pavan et al (66) focused on MEK5 and ERK5 belonging to the same signaling pathway and demonstrated the potential of targeting MEK5 and ERK5 as an anti-metastatic mechanism. Another study used migration ability as a phenotype for functional screening, identifying genes contributing to migration in glioblastoma, a highly invasive cancer (67).…”
Section: Dropout Viability Screening Under Drug Treatmentmentioning
confidence: 99%